Zirconium in the Nuclear Industry: Thirteenth International Symposium 2002
DOI: 10.1520/stp11411s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogen Content on the α/β Phase Transformation Temperatures and on the Thermal-Mechanical Behavior of Zy-4, M4 (ZrSnFeV), and M5™ (ZrNbO) Alloys During the First Phase of LOCA Transient

Abstract: To simulate the end-of-life behavior of cladding tubes during the first phase of a LOCA transient, one may assume that the main effect of a long service exposure on the cladding deformation behavior during LOCA arises from the hydrogen uptake associated with the cladding oxidation at high burn-up. Thus, the recent metallurgical studies and EDGAR [2] tests performed on pre-hydrided Zr-base alloys are presented. The influence of hydrogen has been studied for concentrations ranging from ∼ 100 up to ∼1000 (weight)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 13 publications
2
37
0
1
Order By: Relevance
“…The 38 s cooling time for the ANL tests is long enough for oxygen redistribution during the partial phase change from beta-to-(alpha + beta) in this temperature range. Based on the work of Brachet et al [30], the beta-to-alpha phase transformation is expected to be ≈50% complete at 800ºC for Zry-4 with asfabricated levels of oxygen and with 300-600 wppm hydrogen. The ANL and CEA post-oxidation ductility data are also consistent for samples that were slow cooled from 1200ºC to RT, even though the total cooling time from 1200ºC to 150ºC was much greater for the CEA samples.…”
Section: Discussion On Cooling Rate and Quench Temperature Effectsmentioning
confidence: 99%
“…The 38 s cooling time for the ANL tests is long enough for oxygen redistribution during the partial phase change from beta-to-(alpha + beta) in this temperature range. Based on the work of Brachet et al [30], the beta-to-alpha phase transformation is expected to be ≈50% complete at 800ºC for Zry-4 with asfabricated levels of oxygen and with 300-600 wppm hydrogen. The ANL and CEA post-oxidation ductility data are also consistent for samples that were slow cooled from 1200ºC to RT, even though the total cooling time from 1200ºC to 150ºC was much greater for the CEA samples.…”
Section: Discussion On Cooling Rate and Quench Temperature Effectsmentioning
confidence: 99%
“…As such, extensive studies have been conducted over the past decades on the hightemperature steam-oxidation of fuel-rod cladding made of traditional zirconium alloys, such as Zircaloy-2 (Zry-2) and Zircaloy-4 (Zry-4) [1][2][3][4][5][6][7][8][9]. Advanced zirconium alloys, such as Zr-Sn-Nb and Zr-Nb, exhibit better corrosion resistance than Zry-4 under the operating conditions of pressurized water reactors (PWRs) [10][11][12][13][14][15][16][17][18]. Cladding alloys such as ZIRLO TM (Zr-1 wt.% Sn-1 wt.% Nb) and M5 TM (Zr-1 wt.% Nb) have replaced Zry-4 in most US PWRs, and E110 (Zr-1 wt.% Nb) is used in PWRs designed by the Russian nuclear vender (TVEL).…”
Section: Introductionmentioning
confidence: 99%
“…(2)) considering the oxygen in the "n" phase is an ideal mixture. The motion of layer boundaries is derived from the mass balance of oxygen at the interface between two layers according to equation (3). The oxygen diffusion coefficient is extracted from literature data for each of the a(O) phase and b-phase.…”
Section: Oxygen Concentration Profiles Modelingmentioning
confidence: 99%
“…It was frequently reported that oxygen and hydrogen contents in the prior-b-phase or in the a+b-phase had a combined influence on the cladding post-quenching embrittlement [2][3][4][5][6][7]. It is thus necessary to understand the mechanisms influencing the motion of these two chemical elements to fully describe the post-quench embrittlement.…”
Section: Introductionmentioning
confidence: 99%